Placing Arrows in Directed Graph Layouts: Algorithms and Experiments. (8th January 2022) - Binucci, Carla; Didimo, Walter; Kaufmann, Michael; Liotta, Giuseppe; Montecchiani, Fabrizio
Abstract: We study how to place arrow heads in directed graph drawings aiming at minimizing their overlaps and avoiding intersections between arrow heads and edges. The objective is to support users to correctly and quickly recognize edge orientations, i.e. to deduce unambiguously the edge orientations. Our contribution is two‐fold: (i) We present exact and heuristic algorithms for this arrow placement problem, along with an extensive experimental analysis of these techniques; and (ii) we report on a user study aimed to understand the impact of different arrow placement strategies on performing global and local analysis tasks on directed graph layouts. Abstract : We study how to place arrow heads in directed graph drawings aiming at minimizing their overlaps and avoiding intersections between arrow heads and edges.